A mechanism generating heterogeneity in thyroid epithelial cells: suppression of the thyrotropin/cAMP-dependent mitogenic pathway after cell division induced by cAMP-independent factors (The Rockefeller University Press, 1992)
The mechanisms that generate the intercellular heterogeneity of functional and proliferation responses in a tissue are generally unknown. In the thyroid gland, this heterogeneity is peculiarly marked and it has been proposed that it could result from the coexistence of genetically different subpopulations of thyrocytes. To evaluate the heterogeneity of proliferative responses in primary culture of dog thyrocytes, we asked whether the progeny of cells having incorporated 3H thymidine in a first period of the culture could have a distinct proliferative fate during a second labeling period (incorporation of bromodeoxyuridine revealed by immunofluorescence staining combined with autoradiography of 3H thymidine). No growth-prone subpopulations were detected and the great majority of cells were found to response to either EGF or thyrotropin (TSH) through cAMP. However, only a fraction of cells replicated DNA at one given period and a clustered distribution of labeled cells within the monolayer, which was different for thymidine- or bromodeoxyuridine-labeled cells, indicates some local and temporal synchrony of neighboring cells. The TSH/cAMP-dependent division of thyrocytes preserved their responsiveness to both TSH and EGF mitogenic pathways. By contrast, cells that had divided during a momentary treatment with EGF lost the mitogenic sensitivity to TSH and cAMP (forskolin) but retained the sensitivity to EGF. Since cells that had not divided kept responsiveness to both TSH and EGF, this generated two subpopulations differing in mitogen responsiveness. The extinction of the TSH/cAMP-dependent mitogenic pathway was delayed (1-2 d) but stable. Cell fusion experiments suggest it was due to the induction of a diffusible intracellular inhibitor of the cAMP-dependent growth pathway. These findings provide a useful model of the generation of a qualitative heterogeneity in the cell sensitivity to various mitogens, which presents analogies with other epigenetic processes, such as differentiation and senescence. They shed a new light on the significance of the coexistence of different modes of cell cycle controls in thyroid epithelial cells.